(untitled) (GYMNASIUM, 2011)
This research aims at evaluating the effectiveness of the kinetic program in terms of improving bronchial asthma, by complying with the principles and objectives of respiratory kinetotherapy. Once set up, this disease is irreversible; all the treatment can do is to restrain the descent of spirometry parameters (VEMS) and to improve dyspnoea on effort felt by the patient. Although they may seem feeble, these achievements are of major importance to a bed patient, who, following treatment, succeeds in getting out of the house and in helping himself/ herself.